HUBUNGAN PENGETAHUAN BIDAN, SIKAP BIDAN DAN FASILITAS KESEHATAN DENGAN PELAKSANAAN 10T PADA IBU HAMIL - Amalia, Rizki; Monalisa, Aprilia; Pahlevi, Rizah (JOURNAL OF HEALTH SCIENCE, 2021)
One of them is in some areas the minimum standard of midwifery care examination is no longer "7T" but becomes "10T", including weighing and measuring height, measuring blood pressure, measuring upper arm circumference (nutritional status value), measuring uterine fundal height, determining presentation. fetus and fetal heart rate (DJJ), screening for tetanus immunization status and giving immunizations (TT) if necessary, giving iron tablets of at least 90 tablets during pregnancy, laboratory tests, case management, consultation (counseling) including planning for delivery and prevention of complications (P4K). ) and postnatal family planning. Research objective: to determine the relationship between knowledge, attitudes, and health facilities with the application of 10T in pregnant women. This research is a quantitative research with an analytical survey with a cross sectional approach. The population in this study were all 382 mothers who underwent prenatal care. The sample of this research used simple random sampling method. The sample of this study amounted to 95 respondents. Data analysis was carried out in two stages, namely univariate analysis and bivariate analysis with Chi-square statistical test. The results of the bivariate analysis found that there was a relationship between knowledge (p value = 0.006), attitude (p value = 0.000), and there was a relationship between health facilities (p value = 0.000) and the application of 10T for pregnant women. These suggestions are expected to be taken into consideration in decision making, can improve the quality of services, especially regarding the implementation of 10T in pregnant women. Keywords: knowledge, attitude of midwives, implementation of pregnant women 10T